AB0471 ELEVATED EXPRESSION OF PYRUVATE KINASE M2 IN GIANT CELL ARTERITIS. (2nd June 2020) - Esen, I.; Van Sleen, Y.; Heeringa, P.; Boots, A.; Brouwer, E.
Abstract : Background: Giant Cell Arteritis (GCA) is an inflammatory disease of large and medium vessels. In GCA, expression of interleukin-6 (IL-6), a systemic marker of inflammation, is elevated and it has been shown that treatment with IL-6 receptor blockade (Tocilizumab) is beneficial for GCA patients. 1 To investigate the role of the IL-6 signaling pathway in GCA pathogenesis in more depth, we focused on the metabolic enzyme Pyruvate Kinase M2 (PKM2). PKM2 may exist as a tetramer, a dimer and/or a monomer in the cell. Tetrameric PKM2 acts as a glycolytic enzyme and catalyzes the last steps of glycolysis by converting phosphoenolpyruvate (PEP) to pyruvate and ATP. On the other hand, dimeric PKM2 translocates to the nucleus and mediates gene regulation via its non-canonical protein kinase activity. Dimeric PKM2 regulates hypoxia, IL-1β expression and, phosphorylates signal transducer and activator of transcription 3 (STAT3) which functions downstream of the IL-6 signaling pathway.2 Objectives: To investigate the role of PKM2 in GCA diagnosis and pathogenesis. Methods: Immunohistochemical staining for PKM2 was performed on inflamed (n=8) and non-inflamed (n=4) temporal artery biopsies (TAB) from GCA patients and on TAB from non-GCA (n=9) patients. To detect soluble, dimeric PKM2 in plasma commercially available dimeric PKM2 specific ELISA kit was used. To determine the modulation of dimeric PKM2 by treatment, samples of GCA patients at baseline (n=44), at 6 weeks (n=32) and at 1 year (n=31) after treatment were compared to samples from age- and sex-matched healthy controls (HC, n=45) As a positive control, samples from melanoma patients (n =8) were used. To investigate the role of dimeric PKM2 in the pathogenesis of GCA, we correlated PKM2 plasma levels with markers of inflammation (CRP, IL-6) and markers of angiogenesis (Angpt2, VEGF, YKL40). Statistical analysis included the Mann-Whitney U test for comparing different groups while the Wilcoxon rank test was used for paired samples. Correlations were assessed by Spearman's rank correlation coefficient. Results: High expression of PKM2 was found in inflamed and non-inflamed TABs of GCA patients, while in non-GCA TABs PKM2 was sparsely expressed. Circulating levels of dimeric PKM2 were found elevated in melanoma and in GCA patients at baseline/active disease compared to those in healthy controls. Analysis of 6 weeks and 1 year follow up plasma samples showed that plasma levels of dimeric PKM2 significantly decreased upon treatment. Dimeric PKM2 weakly correlated with CRP at baseline (r=0.399, p=0.048) but not with angiogenesis markers. Conclusion: Dimeric PKM2 plasma levels were found elevated in GCA patients at baseline. PKM2 plasma levels were down modulated by treatment. PKM2 plasma levels weakly correlated with inflammation marker CRP. The data suggest that PKM2 as a marker of glycolysis may have relevance in GCA at diagnosis and for monitoring disease activity. Future studies should aim to validate PKM2 in an independent cohort. Additional studies are needed to determine the molecular mechanism underlying the increase in elevated dimeric PKM2 levels and how this may contribute to IL-6 signaling. References: [1]Samson M, Corbera-Bellalta M, Audia S, Planas-Rigol E, Martin L, Cid MC, Bonnotte B. Recent advances in our understanding of giant cell arteritis pathogenesis. Autoimmunity reviews. 2017;16(8):833-44. [2]Alquraishi M, Puckett DL, Alani DS, Humidat AS, Frankel VD, Donohoe DR, Whelan J, Bettaieb A. Pyruvate kinase M2: A simple molecule with complex functions. Free Radical Biology and Medicine.2019;143:176-192. Acknowledgments: This project received funding from the EU Horizon 2020 research and innovation program under the Marie Sklodowska-Curie grant agreement 754425. Disclosure of Interests: Idil Esen: None declared, Yannick van Sleen: None declared, Peter Heeringa: None declared, Annemieke Boots Consultant of: Grünenthal Gmbh until 2017, Elisabeth Brouwer Consultant of: Roche (consultancy fee 2017 and 2018 paid to the UMCG), Speakers bureau: Roche (2017 and 2018 paid to the UMCG)